2015
DOI: 10.1007/s40609-015-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Utilization of HIV Care Services Among Adolescents and Young Adults in Rakai, Uganda: the Role of Economic Strengthening

Abstract: Background Early entry into HIV care is low in Sub-Saharan Africa. In Rakai, adolescents and young adults 15-24 years were at increased risk of not entering care after knowledge of their positive HIV status. This qualitative study explored barriers to entry into care from HIV-positive clients aged 15-24 years and explored the role of economic strengthening in promoting care utilization. Methods We conducted 18 in-depth interviews among HIVinfected individuals aged 15-24 years, who had not entered care within 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
3
5
2
Order By: Relevance
“…We found that women and PLHIV on ART were more likely to return to HIV care after missing a scheduled clinic visit. This finding is in agreement with prior studies in which gender and ART status were associated with return to care after tracking [ 16 , 20 22 ]. In a systematic review of 42 studies from 12 countries, factors associated with lower retention rates included younger age, male gender, stigma, non-disclosure of HIV status, fear of drug side effects, and transport costs [ 23 ].…”
Section: Main Textsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that women and PLHIV on ART were more likely to return to HIV care after missing a scheduled clinic visit. This finding is in agreement with prior studies in which gender and ART status were associated with return to care after tracking [ 16 , 20 22 ]. In a systematic review of 42 studies from 12 countries, factors associated with lower retention rates included younger age, male gender, stigma, non-disclosure of HIV status, fear of drug side effects, and transport costs [ 23 ].…”
Section: Main Textsupporting
confidence: 93%
“…The proportion of PLHIV who ever missed a scheduled clinic visit in our study is similar to that reported in other studies of mobile populations [ 15 , 16 , 22 ]. Some PLHIV may have cycled in and out of care, given the mobile nature of the study population [ 9 ].…”
Section: Main Textsupporting
confidence: 90%
“…They were unable to meet the financial demands of transport, which made making a walk to the clinic a necessary. Similar findings related to transport issues were reported in other countries such as Uganda (Nakigozi et al, 2015). In resource‐rich countries such as the United States of America (USA) and Australia, specific disadvantaged groups of YLWHIV are often impacted with similar issues, mainly those living in poverty, in society with a limited number of services and without adequate health insurance coverages (Centers for Disease Control & Prevention, 2020, Lea et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Despite the efforts above, SSA countries continue to lack the means of maintaining sufficient utilization and accessibility to these services by their youth population (Akatukwasa et al, 2019). Stigma, lack of confidentiality, inherent poverty, poor clinical reception, lack of governments’ protection against child abuse and societal misconception about sexual reproductive health services, have all been reported in SSA as barriers to service access and utilization (Nakigozi et al, 2015, Sullivan et al, 2019). The under‐utilization of the provided services negatively impacts on HIV knowledge, access to condoms and ART adherence for controlling HIV transmission (Rodger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other factors that act as barriers for adolescent HIV testing uptake include poor accessibility to HTS due to transport, cost, service hours of health facilities, and negative attitudes or behaviors from health providers, including being judgmental and not maintaining confidentiality [ 17 , 18 ]. On a structural level, consent requirements pose barriers for adolescents in accessing testing services.…”
Section: Introductionmentioning
confidence: 99%